Impacts of land-use and climate changes on surface runoff in a tropical forest watershed (Brazil). Issue 11 (17th August 2020) - Lucas-Borja, Manuel Esteban; Carrà, Bruno Gianmarco; Nunes, João Pedro; Bernard-Jannin, Léonard; Zema, Demetrio Antonio; Zimbone, Santo Marcello
ABSTRACT: Surface runoff generation capacity can be modified by land-use and climate changes. Annual runoff volumes have been evaluated in a small watershed of tropical forest (Brazil), using the Soil and Water Assessment Tool (SWAT) model. Firstly, the accuracy of SWAT in runoff predictions has been assessed by default input parameters and improved by automatic calibration, using 20-year observations. Then, the hydrological response under land uses (cropland, pasture and deforested soil) alternative to tropical forest and climate change scenarios has been simulated. SWAT application has showed that, if forest was replaced by crops or pasture, the watershed's hydrological response would not significantly be affected. Conversely, a complete deforestation would slightly increase its runoff generation capacity. Under forecasted climate scenarios, the runoff generation capacity of the watershed will tend to decrease and will not be noticeably different among the representative concentration pathways. Pasture and bare soil will give the lowest and highest runoff coefficients, respectively.